Gating mechanism of hyperpolarization-activated HCN pacemaker channels - Rosamary Ramentol (Nature Portfolio, 2020)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are essential for rhythmic activity in the heart and brain. Here authors reverse the voltage dependence of HCN channels by mutating only two residues located at the interface between the voltage sensor and the pore domain.